Antioxidant evaluation of Helichrysum sp. and Santolina sp. extracts on Saccharomyces cerevisiae cell model - Grčić, Nikola (2016)
Helichrysum italicum (Roth) G. Don fil., H. stoechas (L.) Moench, Santolina chamaecyparissus L. and S. rosmarinifolia L. are species of the Asteraceae family used in Portuguese folk medicine to several illnesses related with oxidative stress. The ethanolic extracts (70%) of these species were studied for the evaluation of their antioxidant bioactivities using Saccharomyces cerevisiae as eukaryotic cell model [1]. H2O2 was used as oxidative agent in the parental strain BY4741 and mutant strains affected in superoxide dismutase – SOD1 and SOD2; the main transcription factor in oxidative stress response – YAP1; catalase – CTT1; and in the three forms of glutathione peroxidase – GPX1, GPX2 and GPX3, in viability assays by assessment of capacity of formation of colonies on plate, when S. cerevisiae cells, strain BY4741, was exposed up to 90 min to 2,5 mM H2O2 and plant extract (PE). At lower concentrations of plant extracts (25 – 50 µg/mL), yeast cell viability was protected when compared with cells exposed only to H2O2, while higher concentrations promoted increased loss of viability. In subsequent experiments with mutant strains, viability was assessed by incorporation of 1.75 mM or 2.25 mM of H2O2 and PE (25 µg/mL) into solid media. Strains affected in SOD1, YAP1 and in GPX1, GPX2 and GPX3 presented higher loss of viability in the presence of H2O2 and PE than H2O2 alone, suggesting that the protective effect of the PE observed in the parental strain BY4741 is dependent on the proteins encoded by these genes. On the other hand strains affected in SOD2 and CTT1 were protected against H2O2, suggesting that these genes are not targeted by PE. Acknowledgements: This work is financially supported by “Fundação de Ciência e Tecnologia” (FCT, Portugal), through PhD fellowship SFRH/BD/52540/2014.